Interaction of inherited genetic variants in the NLRP3 inflammasome/IL-6 pathway with acquired clonal hematopoiesis to modulate mortality risk in patients with HFrEF. (3rd October 2022) - Cremer, S; Katsaouni, N; Abplanalp, W T; Berkowitsch, A; Kirschbaum, K; Rieger, M; Rapp, S; Wild, P; Dimmeler, S; Schulz, M; Zeiher, A
Abstract: Aims: Clonal hematopoiesis (CH), defined as the presence of an expanded somatic blood cell clone due to acquired mutations in leukemia driver genes, was shown to be associated with increased mortality in patients with chronic ischemic heart failure with reduced ejection fraction (HFrEF). Mechanistically, circulating monocytes of mutation carriers display increased expression of proinflammatory genes involved in inflammasome and IL-6 signaling. Inherited single nucleotide variants (SNPs) in the IL-6 pathway are well known to affect inflammatory activation. Therefore, we investigated whether known SNPs in genes encoding for components of the inflammasome/IL-6 signaling pathway modulate fatal outcomes in HFrEF patients with CH. Methods and results: In a total of 446 patients with chronic HFrEF, peripheral blood or bone marrow mononuclear cells were analyzed for the CH driver mutations DNMT3A and TET2 as well as 40 preselected SNPs affecting genes in the NLRP3 inflammasome/IL-6 signaling pathway. The 103 patients carrying a CH driver mutation demonstrated significantly increased mortality compared to the 343 patients without CH mutations (25, 24% vs 13.99% at five years; p=0.0064). We identified three commonly occurring variants known to disrupt IL-6 signaling (rs2228145, rs4129267 and rs4537545) which are in strong linkage disequilibrium and present in more than 50% of CH carriers. As illustrated in Figure 1A, harboring one of those SNPs abrogated the increased mortality risk in patients with HFrEF and CH (p≤0.05 for each SNP). On the contrary, three different SNPs namely rs2250417, which is associated with increased IL-18 levels as well as rs4722172 and rs4845625, which are known to activate IL-6 signaling, were identified to mediate fatal outcomes in patients with HFrEF and CH (p<0.05 for each; Figure 1B). None of the assessed SNPs influenced outcomes in patients without CH. Single cell RNA-sequencing of circulating monocytes of patients with HFrEF revealed increased inflammatory signaling in DNMT3A mutation carriers without protective SNPs with genes upregulated in pathways such as "Cellular response to stress" (FDR −log 24.3), "Regulation of cell activation" (FDR −log 22.7) or "Cytokine signaling in the immune system" (FDR −log18.2). Conclusion: Among CHIP carriers with HFrEF, inherited variants in loci encoding for genes involved in inflammatory signaling associate with mortality. These data not only provide mechanistic insights into inflammatory mechanisms contributing to fatal outcome of HFrEF in CH carriers but may also inform trials evaluating precision-targeted anti-inflammatory therapy in patients with DNMT3A and TET2 mutations and chronic HFrEF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Center of Cardiovascular Research;Cardiopulmonary Institute, Frankfurt, Germany